2020
DOI: 10.3390/resources9090111
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coal’s Petrographic Composition on Its Suitability for the Gasification Process: The Example of Polish Deposits

Abstract: In this paper, we discuss the impact of the rank of coal, petrographic composition, and physico-chemical coal properties on the release and composition of syngas during coal gasification in a CO2 atmosphere. This study used humic coals (parabituminous to anthracite) and lithotypes (bright coal and dull coal). Gasification was performed at temperatures between 600 and 1100 °C. It was found that the gas release depends on the temperature and rank of coal, and the reactivity increases with the increasing rank of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In comparison, the carbon content in fossil fuels increased to over 90% (for anthracite [43]). Bielowicz et al [44,45] presented the chemical analysis of the share of elements in 28 coal samples including low-rank and bituminous coal samples derived from the Coal Basin in Poland and showed that the carbon content ranged from 63.40% (lignite) to 89.73% (coking coal).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the carbon content in fossil fuels increased to over 90% (for anthracite [43]). Bielowicz et al [44,45] presented the chemical analysis of the share of elements in 28 coal samples including low-rank and bituminous coal samples derived from the Coal Basin in Poland and showed that the carbon content ranged from 63.40% (lignite) to 89.73% (coking coal).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the petrographic and mineral composition of the coal deposit, and the properties resulting from this composition, should be the basis for optimizing the conditions in coal preparation plants [6,19,20]. Such an approach makes it possible to control the properties of the final product in order to obtain concentrates with precisely Minerals 2021, 11, 1265 2 of 17 defined parameters and properties, usable in clean coal technologies (CCT), especially in combustion, coking, and gasification processes [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%